The Russian Caucasus Xerophyte Gene Protection - Magomadova, R S; Astamirova, M A-M; Abdurzakova, A S; Dudagova, E Sh; Israilova, S A; Khanaeva, Kh R; Khasueva, B A (IOP conference series. Earth and environmental science, 2021)
The paper provides a scientific and practical justification of the need to preserve the flora gene pool. International and federal legal documents justifying the need for drawing up and keeping Red Lists are specified along with the Methodical Recommendations for Keeping Red Lists, considering by the constituent entities of the Russian Federation in the preparation of relevant regional publications. The total number of the Russian Caucasus xerophytes is specified – 1,018 vascular plant species (ferns, gymnosperms, angiosperms) belonging to 291 genera and 65 families; a consolidated list of species included in the Red Lists of the Russian Federation and 10 subjects of the Russian Caucasus is given, including 368 species (155 genera and 54 families), 118 of which are protected at the federal level. For the flora of each of the entities considered, the total number of xerophilic species, their representation in federal and regional publications, as well as the percentage of species included in the regional Red Lists are indicated. In the study area, 76 endemic and 17 relict species need protection. Three promising areas have been identified where federal-level SPNRs can be arranged to preserve xerophilic floristic complexes.